THE FEASIBILITY OF THE SUSTAINABLE RE-DEVELOPMENT OF UNIVERSITY PLAZA - Derkach, Nick (My University, 2008)
This paper investigates the feasibility of the construction of a sustainable mixed-use development from a 1950's commercial plaza. The specific commercial plaza under investigation was University Plaza in Dundas, Ontario. Incorporating sustainable building techniques, such as higher density housing, clean energy generating technologies, energy efficiency, and water conservation, a more sustainable design for the plaza was accomplished. To become more pedestrian friendly, pedestrian areas were incorporated into the design, as well as a rapid transit terminal. Using rough construction estimates, it was determined that redevelopment would cost $67.9 million± 20% with a simple payback period of 7.8 years. Using the time value of money, a discounted payback period between 9.6 and 16.0 years was determined. As a result, the re-development project was deemed economically feasible to a reasonable degree.
Keywords: Re-development of University Plaza, Road Network Design and Parking